Taxation of Temporary Jobs: Good Intentions with Bad Outcomes?. Issue 626 (22nd November 2019) - Cahuc, Pierre; Charlot, Olivier; Malherbet, Franck; Benghalem, Helène; Limon, Emeline
Abstract: This article analyses the consequences of the taxation of temporary jobs of short duration recently introduced in several European countries to induce firms to create more open-ended contracts and to increase the duration of jobs. The estimation of a job search and matching model on French data shows that the taxation of temporary jobs does not reach its objectives: it reduces the mean duration of jobs and decreases job creation, employment and welfare of unemployed workers.